IMPLIKASI HUKUM TERHADAP SALAH UKUR TANAH MILIK MASYARAKAT OLEH BPN KOTA LANGSA - Ramadhani, Wahyu (P3M, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2020)
Based on Article 1 number (5) Regulation of the Minister of Agrarian (PMNA) Number 3 of 1997 concerning Mapping plots of land is an activity describing the results of measurements of land plots systematically or sporadically by a certain method on certain media such as paper sheets, drafting films or other media so that the location and the size of the plot of land can be known from the media where the mapping of the plot of land is. This research is trying to answer how the legal implications of community land misstatement by BPN and what are the efforts and obstacles of BPN in the settlement of misalignment of community owned land. In this study the authors used normative and empirical juridical research methods. Normative juridical research is research conducted by examining library materials or secondary data. As a result of the Legal Measure of Misuse of Community Owned Land By BPN, in this case we can know that this can be contested and can be canceled due to incorrect measurements of community owned land, especially in the future which can have an effect on landowners in carrying out the sale and purchase deed, therefore the consequences of this law can be said to be administrative defects. In solving cases of community land misstatement here BPN still lacks human resources who understand the mediation of land disputes settlement. This was revealed by Mr. Syahrizal that in resolving land disputes through mediation by the East Aceh District Land Agency, which was carried out by the Deputy for Management, Study and Handling of Land Disputes due to the lack of mediators in the Office.